NDUFA9 point mutations cause a variable mitochondrial complex I assembly defect. Issue 1 (21st November 2017) - Baertling, F.; Sánchez‐Caballero, L.; van den Brand, M.A.M.; Fung, C.‐W.; Chan, S.H.‐S.; Wong, V.C.‐N.; Hellebrekers, D.M.E.; de Coo, I.F.M.; Smeitink, J.A.M.; Rodenburg, R.J.T.; Nijtmans, L.G.J.
Abstract : Mitochondrial respiratory chain complex I consists of 44 different subunits and contains 3 functional modules: the Q‐, the N‐ and the P‐module. NDUFA9 is a Q‐module subunit required for complex I assembly or stability. However, its role in complex I biogenesis has not been studied in patient fibroblasts. So far, a single patient carrying an NDUFA9 variant with a severe neonatally fatal phenotype has been reported. Via exome sequencing, we identified a novel homozygous NDUFA9 missense variant in another patient with a milder phenotype including childhood‐onset progressive generalized dystonia and axonal peripheral neuropathy. We performed complex I assembly analysis using primary skin fibroblasts of both patients. Reduced complex I abundance and an accumulation of Q‐module subassemblies were present in both patients but more pronounced in the severe clinical phenotype patient. The latter displayed additional accumulation of P‐module subassemblies, which was not present in the milder‐phenotype patient. Lentiviral complementation of both patient fibroblast cell lines with wild‐type NDUFA9 rescued complex I deficiency and the assembly defects. Our report further characterizes the phenotypic spectrum of NDUFA9 deficiency and demonstrates that the severity of the clinical phenotype correlates with the severity of the effects of the different NDUFA9 variants on complex I assembly. Abstract :